KOLABORASI PEMERINTAH DESA DAN LEMBAGA ADAT TERHADAP PELESTARIAN KEARIFAN LOKAL DI DESA BANDUR PICAK KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR TAHUN 2014-2016 - Azlin, Desni; Febrina, Rury (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Good development is rooted development and takes into consideration local wisdom that exist in society. Not only the tribal chief but also the role of customary local institutions are required for maintaining and conserving the local wisdom, so modern cultures cannot eliminate them. Moreover, it also need to be supported by the village government. In this paper, the researcher want to study collaborative efforts between village goverment and customary local institutions in conserving the local wisdom which is located at Bandur Picak Village, Koto Kampar Hulu District, Kampar Regency from 2014 to 2016.This research is intended to: (1) to describe the collaboration between village goverment and customary institutions on conserving the local wisdom that exist in Bandur Picak Village from 2014 to 2016, (2) to find out some causes that affect the collaboration between village goverment and customary institution on conserving the local wisdom that exist in Bandur Picak Village from 2014 to 2016. In this paper, the researcher use descriptive research and qualitative approach. This research is conducted in Bandur Picak Village, Koto Kampar Hulu District, Kampar Regency. The researcher uses interviews and documentations as collecting data. Qualitative analysis, on the otherhand, is used to analize the data.The finding of the research sums up that collaboration between village government and customary institutions in preservasing local wisdom at Bandur Picak Village can be seen from various things, that is face to face dialogue between village government and customary institutions is rare, lack of trust between village government and customary institutions, dominance by village government in decision making related to local wisdom conservation in the Bandur Picak Village. As for collaboration between village government and customary institutions influenced by external and internal factors. External factors in the form of lack of funds, the absence of traditional centers, and the dominance of village government. Whereas, internal factors are influenced by the lack of communication between customary stakeholders and the lack of knowledge of the customary institutions.Keywords: Collaboration, Village Goverment, Customary Institutions, Local Wisdom